A mini review on nanorobots in medical field: Applications and challenges - Mubarik, Abdirisak; Sarah ‘Atifah, Saruchi; Mahmud Iwan, Solihin; Teh, Boon Hong; Ng, Weng Kent (Penerbit UMP, 2023)
Technology advancements have expanded our ability to affect the world around us on a progressively smaller scale. Nanotechnology provides substantial advantages over traditional approaches for diagnosis and therapy. Nanorobot development is an intriguing and promising area of nanotechnological research. Nanorobotics is the study of robotics at the nanometer scale, which encompasses nanoscale robots as well as huge robots capable of manipulating things with nanometer resolution in the nanoscale range. Nano-robotic manipulation, with its capacity to position and orient nanometer-scale objects, is a viable technique to build nano-systems, including nanorobots. nanorobotics has provided a ray of hope in various disciplines, particularly in medicine. They are used in medical field for treating cancer, checking blood contents, diagnoses, and accurate drug delivery. This mini literature review focuses on the applications and challenges of nanorobots in the medical field.